Conceptualising patterns of spatial flows: Five decades of advances in the definition and use of functional regions - Klapka Pavel; Halás Marián (Moravian Geographical Reports, 2016)
Some fifty years in the development of ideas about the definition and use of functional regions are elaborated in this article, as an introduction to this Special Issue of the Moravian Geographical Reports. The conceptual basis for functional regions is discussed, initially in relation to region-organising interactions and their behavioural foundations. This paper presents an approach to functional regions which presumes that such regions objectively exist and that they are based on more or less tangible processes (however, a different view of regions is also briefly described). A typology of functional regions is presented and the development of methods for finding a definition of functional regions is discussed, as well as a typology for these methods. The final part of this article stresses the importance of functional regions in geographical research, and introduces some emerging new prospects in the study of functional regions.